Designing Project Baseline Team 2 and Cost Reimbursement Dashboard of Integrated Educational Application Development Project at XYZ Company - Alfarrasi, Muhammad Daffa; Pratama, Devi; Saputra, Muhardi (eProceedings of Engineering, 2023)
Abstract-One of the most critical issues while implementing the project is Project delay. The delay will affect cost overruns and take longer to complete when it is delayed. And the costs that must be expended for a project must be precisely maintained and tracked. this study focused on the design of the baseline scope, baseline schedule, and dashboard of the reimbursement dashboard system. The decomposition method is used to divide the scope or project scope and project results into levels or hierarchical tiers of work to make them more specific and manageable. Designing the schedule baseline using the critical path method (CPM) to calculate the time required to complete the various stages of a project, which is supposed to be precise as well as the relationship between the resources utilized and the time required to complete the project. The design of the cost reimbursement dashboard is based on the issues stated in this project because the reimbursement process is still conducted manually, making it difficult to monitor and control expenses. By utilizing this dashboard, it is expected that users and other stakeholders will be able to streamline each step of this expense reimbursement.Keyword- scope baseline, schedule baseline, cost reimbursement